Factors Affect Budget Absorption In Government Institutions of South Sulawesi - Darwis Lannai; Asbi Amin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
The purpose of this study was to analyze and study the effect of financial regulations, budget absorption, apparatus competence, bureaucratic environment, and organizational commitment to budget absorption by the South Sulawesi Provincial Government to be able to provide input for the policies of the South Sulawesi Provincial Government in maximizing budget absorption. This study's population was all employees of the South Sulawesi Provincial Government. They determined the sample using the technique Judgment Sampling by selecting 2 State Civil Servants represented by the Head of the regional apparatus organization Office as the Budget User Authority and Commitment Making Official at each Provincial Office. South Sulawesi so that a total of 54 samples were obtained. This study uses a quantitative approach with multiple regression analysis methods. The study results state that financial regulation, budget absorption, competence, bureaucratic environment, and organizational commitment have a positive and significant effect on budget absorption. This result implies that the community's interests always guide the South Sulawesi Provincial Government in every action and activity as principles in the planning and implementation process budgeting.